EDUCATION AS INTERDISCIPLINARY KNOWLEDGE: PRODUCTION, THEORY AND PRACTICE – IN SEARCH OF AN ESSAY - Emanuel Oliveira Medeiros (European Scientific Journal, ESJ, 2015)
Throughout the text, we will be combining a dialogue of experiential construction and knowledge, linking methodology and object, a method that by its nature should be integrated by mobilising processes and procedures of various genres. We will analyse some aspects of Education as an Interdisciplinary Area and Field of Knowledge in theoretical and theoretical and practical terms. We will highlight the concepts of multidisciplinary, interdisciplinary, and transdisciplinary, having in mind the cross-cutting dynamics of Curriculum and Knowledge. We will mention authors whose quite relevant studies potentiate an integrated curricular perspective that integrates Training, particularly the Multidimensional Training of Teachers. We will mention some legislation passed as part of the Portuguese Educational System, which helps understand the efforts to introduce interdisciplinary practices in the curriculum at the various levels of education in line with European and even global conceptions. We will highlight, among other possibilities, various areas of knowledge and specialties that substantially contribute – or could contribute – towards interdisciplinary reflection and work, particularly Philosophy of Education and Philosophy of Curriculum.